KINERJA APBD KABUPATEN/KOTA DI SUMATERA SELATAN - Didik Susetyo (Jurnal Ekonomi Pembangunan, 2008)
This research aimed to see the sequence level of "Anggaran Pendapatan dan Belanja Daerah (APBD)” or local budget implementation based on effectiveness and efficiency, the growth of APBD, local finance capability indicators, and elasticity of local real income. Data used in this research was secondary data and panel data from 2004 until 2006 in ‘kabupaten/kota in South Sumatra. The analysis technique that used in this research were effectivenesss, efficiency, the growth of estimate and realization, local finance capability, elasticity concept, and by using Kolmogorov Smirnov and Mann-Whitney Test. The analysis result showed that Musi Banyuasin District has the first sequence level of "APBD” implementation, and Musi Rawas District has the last sequence level of "APBD” implementation. Elasticity of PAD to real income showed that Palembang City had elastic and the other ‘kabupaten/kota' had inelastic. Meanwhile, the result of Kolmogorov Smirnov showed that was significance differences of "APBD” implementation among districts/cities in South Sumatera. The result of Mann-Whitney Test showed that was no significance differences of "APBD” implementation between districts/cities. Key Words: APBD, performance, local real income, elasticity, district/city